The role of fiscal policy: A survey of recent empirical findings - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2023)
DSGE models based on New Keynesian principles, which have been extended to allow for banking, the zero lower bound on interest rates (ZLB), and varying price duration, can account well for recent macroeconomic behavior across a variety of economies. These models Önd that active Öscal policy can contribute to macroeconomic stability and welfare by reducing the frequency of hitting the ZLB. Fiscal policy can also share the stabilisation role with monetary policy, whose eectiveness under the ZLB is much reduced.
Keywords: E17; E31; E32; E42; E52; E62; 330; Moments; fiscal policy; zero bound; monetary policy; DSGE model; macro stability; indirect inference